OVERVIEW SERVICE ACTION EMERGENCY PATIENT IN RSUD ERROOM H. ABDUL MANAP JAMBI CITY - sihombing, Elprida; Rudini, Dini; Oktarina, Yosi (Program Studi Keperawatan Universitas Jambi, 2024)
The Emergency Department is a unit that plays a major role in the implementation of emergency management in a crisis or emergency situation for patients with a threatened health status. ED room. This research method uses descriptive observational qualitative design. The sample in thisstudy were 70 respondents. sampling technique using the Lameshow formula with a confidence level of 90% and a large deviation of 20% or 0.3. The results of the Overview of Patient Service Research in the Emergency Room of RSUD H Abdul Manap Jambi City the characteristics of respondents based on service procedures were carried out the most, namely giving oxygen with a total of 52 respondents (74.28%), the mostcommon action was providing infusion assistance by 49 respondents (70%), patients with OPA assistance were 3 respondents ( 4.28%), patients with BVM assistance were 5 respondents (7.14%), patients with Neck collar assistance were 2 respondents (2.85%), GCS examination were 68 respondents (97.14) and blood tests were 65 respondents (92.85%). The conclusion from the results of this study can be concluded that the nursesin the emergency room of RSUD H. Abdul Manap Jambi City are quite good in patient care when receiving incoming patients and are supported bythe category of patients who get complete and good service, namely 65 respondents (92.85%).